Morphometric Analysis of Human Occipital Condyle and its Clinical Significance (GAIMS Journal of Medical Sciences, 2024)
Background: There are several approaches to operate on brainstem and craniovertebral lesions and involve a resection of occipital condyles (OC). Morphological assessment of occipital condyles, aids in determining the extent and direction of condylar drilling, helping to prevent occipito-cervical destabilization and accidental damage to the neurovascular structures related here.Aim: To analyze the morphometry of occipital condyles and the frequency of occurrence of different morphological types of occipital condyles and its clinical significance.Materials and Methods: 100 dry human skulls were studied in the Department of Anatomy, K. J. Somaiya Medical College, Mumbai. The dimensions of the occipital condyles, including their length, width, height and shape were measured. In addition to this, the anterior and posterior intercondylar distances and the distance from the posterior end of the occipital condyle to the hypoglossal canal were recorded using digital Vernier calipers. Paired ‘t’ test was used for significance between the length, width and height of occipital condyles with that of its sides (right and left respectively).Results: The mean measurements of the occipital condyles in terms of length, width, and height were identified as 23.52, 23.13 and 9.49 mm respectively. As the value of p was less than 0.05, the differences between right and left side were insignificant. The average anterior intercondylar distance and posterior intercondylar distance was found to be 21.16 mm and 43.35 mm respectively. Commonest shape seen was oval in 38% of skulls followed by “S” shaped condyle in 22% skulls. On an average, the hypoglossal canal was positioned 8.78 mm from the posterior end of the occipital condyles.Conclusions: These results confirm the variability in different parameters of occipital condyles. The safest area of the occipital condyles to be resected is maximum up to 12mm from the posterior end because there is no location for the hypoglossal canal orifice.